Manipulative monkeys : the capuchins of Lomas Barbudal - Perry, Susan, 1965-; Manson, Joseph H. (Electronic books., 2008)
This book takes us into a Costa Rican forest teeming with simian drama, where since 1990 primatologists Perry and Manson have followed four generations of capuchins. The authors describe behavior as entertaining--and occasionally as alarming--as it is recognizable: competition and cooperation, jockeying for position and status, peaceful years under an alpha male devolving into bloody chaos, and complex traditions passed from one generation to the next. Interspersed with their observations are the authors' colorful tales of the challenges of tropical fieldwork.